TAMI-12. CANCER-IMMUNE CELL INTERACTIONS DRIVE TRANSITIONS TO MESENCHYMAL-LIKE STATES IN GLIOBLASTOMA. (12th November 2021) - Hara, Toshiro; Chanoch-Myers, Rony; Mathewson, Nathan; Myskiw, Chad; Atta, Lyla; Bussema, Lillian; Eichhorn, Stephen; Greenwald, Alissa; Kinker, Gabriela; Rodman, Christopher; Castro, L Nicolas Gonzalez; Wakimoto, Hiroaki; et al.
Abstract: Communication between cancer cells and immune cells is a key determinant of the glioblastoma ecosystem and its response to therapies, but remains poorly understood. Here we leveraged single-cell RNA-sequencing (scRNA-seq) of human samples and mouse models, deconvolution analysis of bulk specimens from The Cancer Genome Atlas (TCGA) and functional approaches to dissect cellular states and cross-talk in glioblastoma. We demonstrate that macrophages induce a transition of glioblastoma cells into mesenchymal-like (MES-like) states. This effect is mediated, both in vitro and in vivo, by macrophage-derived Oncostatin M (OSM) and its cognate receptor OSMR on glioblastoma cells. We show that MES-like glioblastoma states are associated with increased T cells cytotoxicity and potentially with better clinical response to immunotherapies. Overall, our work dissects the cellular interactions within the glioblastoma microenvironment, with potential implications for therapies.